Penerapan Metode User Centered Design dan WebQual 4.0 dalam Pengembangan Sistem Informasi Desa Wisata Punden Gunung Cigrek - Christine; Riyadi , Teguh (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2023)
User-centered design (UCD) and WebQual 4.0 are two methods that are commonly used to develop high-quality information systems. This research applied these methods in the context of developing a tourism information system for Punden Gunung Cigrek village in Indonesia. UCD was used to collect user needs and preferences through interviews and observations, while WebQual 4.0 was used to evaluate the quality of the system based on six dimensions: usability, usefulness, information quality, service interaction, trust, and loyalty. The study found that the application of UCD and WebQual 4.0 was effective in improving the quality of the tourism information system for Punden Gunung Cigrek village. UCD helped researchers to obtain user needs and preferences, which were then implemented in the information system. Meanwhile, WebQual 4.0 allowed for a holistic evaluation of the system's quality based on six dimensions. This research demonstrates the effectiveness of using UCD and WebQual 4.0 in developing high-quality information systems for tourism. In future research, these methods could be applied in other locations to improve tourism information systems.